Culture, Region, and Cross‐National Violent Crime1. Issue 2 (20th February 2018) - Corcoran, Katie E.; Stark, Rodney
Abstract : Past cross‐national crime research has focused on structural factors with considerably less attention paid to cultural predictors. We extend the culture of honor thesis by identifying the importance of cultural gender inequality and test a direct measure of it on cross‐national violent crime rates. While prior research typically uses regional variables as proxies for culture, by using a direct cultural measure we are also able to identify whether culture contributes to explaining the regional associations found previously. Based on national surveys of 153 nations and more than a million respondents, this study is able to explore cultural, structural, and regional predictors of violent crime rates cross‐nationally. Two regions, Latin America and sub‐Saharan Africa, are far above the rest of the world in terms of violent crime rates. It turns out that most of the standard structural variables found to be important in previous cross‐national studies no longer have significant effects when controls for these two regions are imposed. On the other hand, we find that our measure of cultural gender inequality has one of the largest associations with violent crime rates, net of region, and also explains portions of both regional associations.